Acute Fatty Liver of Pregnancy: A Rare Case Further Complicated with Disseminated Intravascular Coagulation - Junita, Nuria; Bernolian, Nuswil (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: An acute fatty liver of pregnancy is a rare and potentially deadly pregnancy complication. A case of acute fatty liver of pregnancy that is complicated with disseminated intravascular coagulation is hereby presented.Case Report: A 27-years old, 36 weeks pregnant female is presented with jaundice, elevated LDH and liver enzymes, and thrombocytopenia. An emergency obstetric ultrasonography examination found an unremarkable pregnancy without a placental abruption. The patient was managed conservatively and she delivered 6 days after the presentation. The neonate was treated in the neonatal intensive care unit due to a meconium aspiration. The patient suffered from a continued uterine bleeding and she was managed with the Sayeba’s technique. The laboratory work-up showed a disseminated intravascular coagulation with anemia and thrombocytopenia. The patient was treated with a packed red cell and fresh frozen plasma transfusion. The patient required an intensive care treatment. Discussion: An acute fatty liver of pregnancy is a potentially deadly complication of pregnancy and it requires a multidisciplinary, intensive support. The acute fatty liver of pregnancy symptoms are similar to those of a HELLP syndrome. An acute fatty liver of pregnancy requires a prompt delivery followed with a intensive support. Complications of an acute fatty liver of pregnancy include a hepatic failure and a disseminated intravascular coagulation which should be managed accordingly.Conclusion: An acute fatty liver of pregnancy requires a prompt diagnosis and treatment to achieve the best possible maternal outcome.Acute Fatty Liver of Pregnancy: Kasus Jarang Dengan Komplikasi Koagulasi Intravaskular DiseminataAbstrak Pendahuluan: Acute fatty liver of pregnancy adalah komplikasi kehamilan yang langka dan dapat mematikan. Laporan ini memaparkan sebuah kasus acute fatty liver of pregnancy dengan komplikasi koagulasi intravascular diseminata.Laporan Kasus: Seorang perempuan berusia 27 tahun, hamil 36 minggu datang dengan icterus, peningkatan kadar LDH dan enzim hati, serta trombositopenia. Pemeriksaan ultrasonografi obstetric di IGD menemukan kehamilan tanpa komplikasi dan tanpa solusio plasenta. Pasien ditatalaksana secara konservatif dan melahirkan 6 hari pasca-perawatan. Neonatus dirawat di ruang rawat intensif karena aspirasi meconium. Pasien mengalami perdarahan uterus dan ditatalaksana dengan kondom Sayeba. Pemeriksaan laboratorium menunjukkan adanya koagulasi intravaskular diseminata dengan anemia dan trombositopenia. Pasien ditatalaksana dengan transfuse packed red cell dan fresh frozen plasma. Pasien memerlukan perawatan intensif. Pembahasan: Acute fatty liver of pregnancy adalah komplikasi kehamilan yang dapat mematikan dan memerlukan tatalaksana intensif multidisipliner. Acute fatty liver of pregnancy memiliki gejala yang menyerupai sindrom HELLP. Acute fatty liver of pregnancy ditatalaksana dengan melakukan persalinan diikuti dengan terapi intensif. Komplikasi acute fatty liver of pregnancy meliputi gagal hepar dan koagulasi intravascular diseminata yang harus ditatalaksana dengan tepat.Kesimpulan: Acute fatty liver of pregnancy memerlukan diagnosis dan tatalaksana yang cepat untuk meningkatkan luaran maternal.Kata kunci: acute fatty liver of pregnancy, koagulasi intravascular diseminata, komplikasi kehamilan